Female self-employment and demand for flexible, nonstandard work schedules. - Lombard, Karen V. (Economic Inquiry, 2001)
Motivated by the rising importance of female self-employment, this article develops and estimates a two-step empirical model to explain why married women choose self-employment over wage-salary employment. The article also develops a bounded influence regression model to estimate self-employment wage equations. In sum, a woman is more likely to choose self-employment the greater her relative earnings potential as self-employed, the greater her demand for flexibility, the greater her demand for a nonstandard work week, and if her husband has health insurance. The increase in women's earnings potential as self-employed explains most of the increase in their self-employment from 1979 to 1990. (JEL J23, J22, J31, C13) Reprinted by permission of the publisher.